In-service teachers' mathematical problem solving skills. (March 2020) - Hiltrimartin, C; Hartono, Y; Indaryanti,
Abstract: This study aims to describe the problem-solving skills of in-service teachers. The background of this study is because teachers are less concerned with developing problem-solving skills and rarely gave problem-solving problems. The research method used is a qualitative method. The research subject are the in-service teacher. The data collected with the test technique, in the form of a problem-solving item. The results showed that the ability of teachers in large solutions is still lacking because teachers still have difficulty.